Peningkatan Nilai Tambah Ampas Kelapa Menjadi Aneka Produk Olahan Pangan di Desa Tirto Asri Kecamatan Taluditi Kabupaten Pohuwato - Liputo, Siti Aisa; Bakari, Yuliana (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
This service activity aims to increase the income of traditional coconut oil farmers and processors in Tirto Asri Village, Taludity  District, Pohuwato Regency, with the Zero Waste method, which is processing all the waste produced into innovative and marketable products. In this TEMATIK KKN activity, the community and farmers will be given knowledge and skills regarding coconut-based processed products, especially coconut dregs products as a learning medium and foster a sense of student concern for the problems faced by the community. The method used in this is to use a participatory approach, namely implementing community education and training with academics (field supervisors and students) and the government acting as a facilitator to be able to learn from each other, share knowledge and experiences. The location of the activity is Tirto Asri Village, Taluditi District, Pohuwato Regency. The number of students involved in this activity consisted of 31 people. Meanwhile, the partners of this activity are farmer groups in Tirto Asri Village. The implementation of this activity consists of several programs, namely a program to process coconut dregs into several products, such as brownies, cookies and chocolate balls. The core program activities will be carried out at the village office on September 17, 2020. In addition, additional programs will be carried out by KKN students such as arranging yards and planting vegetable and fruit plants in residents' yards, affixing village aid recipient labels at people's homes, sports activities, and several other activities.